The Effect of Global Oil Prices and Monetary Variables on Inflation in Indonesia - Kayla Khairinnisa Junaidi; Rustam Effendi; Muhammad Nasir (Grimsa Journal of Business and Economics Studies, 2026)
This study aims to analyze the effects of global oil prices, interest rates, and exchange rates on inflation in Indonesia in both the long and short run. Inflation is one of the main indicators of macroeconomic stability, making it important to understand the factors that influence its movements. Such an understanding can assist policymakers in formulating appropriate policies to maintain price stability in Indonesia. This study uses secondary time-series data in the form of monthly observations covering the period from 2015 to 2024, comprising 120 observations. The Error Correction Model (ECM) is employed as the analytical method. The long-run estimation results indicate that global oil prices and interest rates have a positive and significant effect on inflation, while the exchange rate has a negative and significant effect on inflation in Indonesia. In the short run, only the interest rate has a positive and significant effect on inflation, whereas global oil prices and the exchange rate do not have a significant effect. The Error Correction Term (ECT) coefficient of -0.1015, with a probability value of 0.0049, indicates a statistically significant adjustment toward the long-run equilibrium. Overall, the findings suggest that global oil prices, interest rates, and exchange rates play important roles in influencing inflation in Indonesia. Therefore, appropriate monetary policies, including prudent adjustments to interest rates, are necessary to maintain price stability.